Random Thoughts - India Ministry of Community Development (New Delhi)
Random thoughts, Vol II. is a continuation of Vol I, which ended with the Administrator's monthly letter of December, 1955. As in the case of earlier volume, no attempt has been made to edit the letters nor any portions have been left out. The letters, complete up to the end of 1956, have been published chronologically.
Keywords: Community development